2022
DOI: 10.1152/ajpheart.00385.2022
|View full text |Cite
|
Sign up to set email alerts
|

Role of adropin in arterial stiffening associated with obesity and type 2 diabetes

Abstract: Adropin is a peptide largely secreted by the liver and known to regulate energy homeostasis; however, it also exerts cardiovascular effects. Herein, we tested the hypothesis that low circulating levels of adropin in obesity and type 2 diabetes (T2D) contribute to arterial stiffening. In support of this hypothesis, we report that obesity and T2D is associated with reduced levels of adropin (in liver and plasma) and increased arterial stiffness in mice and humans. Establishing causation, we show that mesenteric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 217 publications
1
9
0
Order By: Relevance
“…Circulating adropin levels correlate with vascular function. (7-10) Analysis of standing and prone heart rate and blood pressure recorded on the same visit used to collect the plasma samples used for adropin measurement suggested a relationship. Simple modelling indicated a positive correlation between heart rate measured in the standing (π=0.159, P<0.001, N=448) or prone positions (ρ=0.105, P<0.05, N=447).…”
Section: Resultsmentioning
confidence: 99%
“…Circulating adropin levels correlate with vascular function. (7-10) Analysis of standing and prone heart rate and blood pressure recorded on the same visit used to collect the plasma samples used for adropin measurement suggested a relationship. Simple modelling indicated a positive correlation between heart rate measured in the standing (π=0.159, P<0.001, N=448) or prone positions (ρ=0.105, P<0.05, N=447).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, low serum adropin concentrations did not correlate with severe obesity, diabetes, or systemic markers of inflammation or neuropathy. Recent experiments using mice and cultured cells indicate that deficits in cerebrovascular blood flow, protection of the blood brain barrier, and synaptic functions could be involved 3,5,7,8,30,32 .…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of adropin correlate with indices of glucose and lipid metabolism [1][2][3][4] . Here we also observed correlations between serum adropin concentrations and serum indices of metabolic homeostasis.…”
Section: Inclusion Of Cardio-metabolic Risk Factors Strengthens the C...mentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical significance of adropin levels in different patient populations remains controversial. There is numerous evidence that overweight/obese/T2DM patients had lower adropin levels than healthy volunteers and that a decreased adropin level was associated with a risk of renal dysfunction in patients with T2DM [ 21 , 22 , 23 , 24 ]. Another study reported that elevated serum levels of adropin correlated with a low risk of carotid atherosclerosis in T2DM patients [ 25 ].…”
Section: Introductionmentioning
confidence: 99%